Remote teaching in nursing teaching: reflections on instructional design in the Covid-19 Pandemic (Research, Society and Development, 2021)
Objective: to describe instructional design strategies in remote teaching in undergraduate nursing disciplines in times of Pandemic. Methods: This is a theoretical essay of reflective analysis on the importance of instructional design in remote teaching in undergraduate nursing disciplines with a view to proposing an interactive teaching. Reflective analysis is based on pedagogical strategies with a view to evaluating activities in an interactive way, seeking the exchange of knowledge. Results: as a mediator of knowledge, the teacher must seek content and activities aimed at collaborative learning. Final Considerations: Instructional Design must be constantly built and re-evaluated with extensive use of the tools of the virtual learning environment.